Oxygen storage capacity of Sr3Fe2O7−δ having high structural stability1. Issue 25 (7th July 2015) - Beppu, Kosuke; Hosokawa, Saburo; Teramura, Kentaro; Tanaka, Tsunehiro
<x xml:space="preserve">Abstract</x> Sr3Fe2O7−δ has not only high structural stability under severe reduction conditions, but also high oxygen storage capacity due to topotactic oxygen intake/release.